Russian-Chinese Educational Cooperation in the Pandemic and Post-Pandemic Periods - T. L. Guruleva; Luo Wanqi (Высшее образование в России)
The purpose of the research is to characterize the Russian-Chinese educational cooperation during the pandemic and post-pandemic periods, as well as to assess its future prospects. The timeframe of the study includes the period of the coronavirus pandemic (January 2020 – May 2023) and the post-pandemic period (May 2023 – June 2024). The primary research methods employed in the article are the analysis of open data sources, comparative data analysis, expert surveys, as well as techniques of synthesis, abstraction, and generalization.The study revealed several characteristics of the Russian-Chinese educational cooperation system during the studied period. The system established before the pandemic demonstrated its viability and adaptability, particularly through the utilization of video conferencing, e-learning, and distance educational technologies as main tools. At the same time, it was possible to maintain the traditional offline format of education. However, a decrease in the total number of Chinese and Russian students in both countries was observed, along with a decline in the quality of education due to the transition from offline to online learning.During this period, existing forms of cooperation continued to develop. They include the opening of new joint educational institutions, the implementation of new network university programs, expanding online learning opportunities, creating new forums and associations of universities, strengthening government support for students studying in Russia and China, opening new centers for Russian research in China, etc. Additionally, a mixed format for implementing educational cooperation projects appeared.Furthermore, we identified promising areas for further development of educational cooperation. These include the optimization of the work of the Subcommittee on Educational Cooperation, the introduction of certain concepts related to the functioning of the educational cooperation system into Russian legal practice, the establishment of joint Russian-Chinese educational institutions in Russia. Other potential development areas encompass further optimization of network universities’ activities, the establishment of a multilateral university ranking system, strengthening state support for talented Russian and Chinese students, and a significant increase in the number of individuals studying and using Chinese and Russian languages in both countries.